A study of snakebite cases in a tertiary care hospital in South India, Telangana - Bommineni, Sashidhar Reddy; Rajeshwar, K.; Reddy, P. Durga; Vindhya, T.; Reddy, P. Sai Bhargav; Lakkam, Vamsi Kiran (International Journal of Research in Medical Sciences, 2025)
Background: Snake bites pose a significant global health threat leading to substantial morbidity and mortality. According to WHO, approximately 11,000 deaths occur due to snake bite per annum in India. This study is done to know about common types of snakes in local areas, identify the clinical features, complications and mortality rates in snakebite victims attending RVM Charitable trust hospital. Methods: A hospital-based cross sectional study done from 1st January 2024to 31st December 2024. Fifty patients enrolled during this period. Features during presentation and subsequent period were noted, anti-venom was given accordingly and outcome was recorded. Data was collected in a predesigned data sheet form and was analyzed accordingly. Results: Among 50 snake bite patients, 70% were male and 56% cases were poisonous bites. The common victims were farmers (53%) and the bite was commonly encountered during rural foot walking (32%). Among 28 poisonous cases, 18 Poisonous cases developed neurological manifestations and 3 cases developed breathlessness which required mechanical ventilation support. Rest 10 Poisonous cases developed hematological manifestations and 6 cases developed Acute Kidney Injury of which 3 cases required hemodialysis support. Among the 28 venomous snake bite cases 25 (89%) recovered completely after getting polyvalent antivenom serum and 3 (11%) died after admission. Total 80% cases recovered with 10 vials of polyvalent antivenom serum. No reaction to anti-snake venom was noticed. Conclusions: Snake bites cases are still a serious health problem for us. Treatment of poisonous snake bite with polyvalent antivenom serum is successful and safe. Awareness should be created among the rural people through mass media regarding the complications of snake bite and the need to visit a hospital as early as possible. Availability of snake venom kits should be made in rural health centres to identify the type of snake bite.